2014
DOI: 10.1297/cpe.23.35
|View full text |Cite
|
Sign up to set email alerts
|

Results from 28 Years of Newborn Screening for Congenital Adrenal Hyperplasia in Sapporo

Abstract: Abstract.The primary goal of newborn mass screening (MS) for congenital adrenal hyperplasia (CAH) is the prevention of life-threatening salt-wasting crisis in the most severe forms of CAH, and MS for CAH has been implemented in several countries. We summarize here our experience and results from newborn CAH MS from 1982 to 2010 in Sapporo City. During these 28 yr, the level of 17-hydroxyprogesterone (17-OHP) was determined in MS of samples from 498,147 newborns. During this period, 26 individuals (19 females a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
20
1
1
Order By: Relevance
“…During the study period in São Paulo state, no CAH diagnosis with negative screening was reported. A widely considered cause of false‐negative screening results is perinatal treatment with corticosteroids; however, the newly proposed NBS cut‐off level was able to identify the one salt waster that received antenatal glucocorticoid therapy. We recognize that this study has some limitations and that the false‐negative rate could be underestimated due to patients with CAH that remain undiagnosed, patients who moved out of the state, or infants who passed away with unidentified CAH.…”
Section: Discussionmentioning
confidence: 96%
“…During the study period in São Paulo state, no CAH diagnosis with negative screening was reported. A widely considered cause of false‐negative screening results is perinatal treatment with corticosteroids; however, the newly proposed NBS cut‐off level was able to identify the one salt waster that received antenatal glucocorticoid therapy. We recognize that this study has some limitations and that the false‐negative rate could be underestimated due to patients with CAH that remain undiagnosed, patients who moved out of the state, or infants who passed away with unidentified CAH.…”
Section: Discussionmentioning
confidence: 96%
“…The survey covered >80% of patients who were theoretically calculated by the reported prevalence of 21-OHD in Japan [10, 11], indicating that this study provided representative data for Japanese children with 21-OHD. Based on the results of the survey, pediatric endocrinologists should acknowledge that adrenal crisis is not rare and still potentially associated with fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports review NBS expansion activities across the region. [141][142][143][144][145][146][147][148][149] At the time or our 2007 report, 6 only Australia, New Zealand, and Taiwan included expanded metabolic screening with MS/MS in their screening panels. 6 Since that time, other countries in the Asia Pacific region have expanded to include not only additional metabolic screening, but also a number of other conditions not in their panels at that time.…”
Section: Asia Pacificmentioning
confidence: 99%